Efektivitas Koordinasi Antara Perancang dan Pemrakarsa dalam Harmonisasi Melalui E-Legal Drafting: Studi Kanwil Kemenkum Jatim (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This research aims to examine how coordination between the Legislation Drafter and the Initiator in the harmonization process through the E-Legal application. The harmonization process was previously carried out manually which was then transformed using the E-Legal application which made it easier for the Legislation Drafter and the Initiator to carry out their duties and functions. This research method uses a qualitative method with a case study approach, data collection techniques using interview techniques as primary data and literature study as secondary data. E-Legal application has a great impact on accelerating the harmonization process, although there are still technical and administrative obstacles in its implementation. The results of this study are expected to provide academic and practical understanding.